Abstract P3-01-13: Association between the histopathological growth patterns (HGP) of liver metastases (LM) and survival after hepatic surgery in patients with oligometastatic breast cancer (BC) - Peter B Vermeulen; Ali Bohlok; Sophia Leduc; François Richard; Lara Botzenhart; Michail Ignatiadis; Philippe Aftimos; Christos Sotiriou; Martine Piccart; Alain Hendlisz; Steven Van Laere; Luc Y Dirix; et al. (Cancer Research, 2020)
Abstract Background. Liver is the 3rd most common site for metastatic disease in BC. The proportion of patients with BC LM presenting with so-called oligometastatic disease is estimated to be ~10%. Some of these patients have an indolent disease course after hepatic surgery. However, as of today, it is impossible to identify the ideal candidates for hepatic surgery based on standard clinico-pathological characteristics. Two main HGP have previously been identified in LM from colorectal cancer patients1: (i) the desmoplastic HGP with angiogenesis, inflammation and a rim of fibrous tissue that separates the cancer cells from the liver parenchyma, and (ii) the replacement HGP, with vessel co-option, no angiogenesis, and cancer cells growing into the liver parenchyma while replacing the hepatocytes, with minimal inflammation. This replacement HGP was associated with worse survival and lack of benefit from bevacizumab in patients operated for colorectal LM2. Here, we aimed at characterizing HGP of LM from BC patients who underwent hepatic surgery. Patients and methods. We considered a series of 36 consecutive patients with invasive BC from Institut Jules Bordet and Hôpital Erasme, Brussels, who underwent surgical resection of LM. Patients were operated between April 2000 and October 2017, and the median follow-up was 10.7 years. The HGPs of resected LM were scored according to international guidelines on H&E stained section by light microscopy3, by a pathologist (PV) blinded to outcome data. All sections of all LM were evaluated for each patient. Associations between HGP and clinico-pathological characteristics were assessed using the Fisher exact test, and associations with progression-free (PFS) and overall survival (OS) using Cox proportional hazard regressions considering date of hepatic surgery as the starting time. Age at hepatic surgery, ER and HER2 status of the LM, and presence of extra-hepatic metastasi(e)s were considered as adjustment variables and centre as stratification factor. Results. In 16 patients (44%) the LM exclusively presented the replacement HGP (pure-replacement group) while in the remaining 20 patients (56%) the LM were at least partly desmoplastic (any-desmoplastic group). There was no association of HGP with ER or HER2 status of primary BC or LM. LM subtypes were as follows: 2 ER-/HER2- (7%), 11 HER2+ (38%), 16 ER+/HER2- (55%)- information is currently missing for 7 patients. In 10/30 (33.3%) patients, ER-status changed in the LM compared with the primary BC (8 losses, 2 gains). Significantly more patients in the any-desmoplastic group had a primary BC without lymph node metastases (56% versus 21% in the replacement group, p=.02). Survival analyses showed that any-desmoplastic HGP was independently associated with increased PFS after liver surgery when compared with pure-replacement HGP (Hazard Ratio, HR, 0.34; 95% CI: 0.12-0.96; p=.041). All patients with pure-replacement HGP relapsed within the first two years after hepatic surgery. The other factors in the model were not significantly associated with PFS. Similar results were observed for OS (adjusted HR for HGP: 0.26; 0.07-1.01, p=.052). Conclusion. In this study, we showed evidence that the pure-replacement HGP of BC LM is related to worse outcome after hepatic surgery, corroborating our findings in patients with colorectal LM1. These findings, which are currently being validated in additional series, suggest that HGP of LM could represent a promising candidate marker of oligometastatic progression in BC. Refs: 1. doi:10.1007/s10456-019-09661-5; 2. doi:10.1038/s41571-019-0181-9; 3. doi:10.1038/bjc.2017.334. Citation Format: Peter B Vermeulen, Ali Bohlok, Sophia Leduc, François Richard, Lara Botzenhart, Michail Ignatiadis, Philippe Aftimos, Christos Sotiriou, Martine Piccart, Alain Hendlisz, Steven Van Laere, Luc Y Dirix, Jean-Christophe Noël, Valerio Lucidi, Elia Biganzoli, Denis Larsimont, Christine Desmedt, Vincent Donckier. Association between the histopathological growth patterns (HGP) of liver metastases (LM) and survival after hepatic surgery in patients with oligometastatic breast cancer (BC) [abstract]. In: Proceedings of the 2019 San Antonio Breast Cancer Symposium; 2019 Dec 10-14; San Antonio, TX. Philadelphia (PA): AACR; Cancer Res 2020;80(4 Suppl):Abstract nr P3-01-13.